BARRIERS TO TRANSFORMATIVE CLIMATE CHANGE EDUCATION: MITIGATION AND RESILIENCE-BUILDING - Josephine Oranga; Billiah Gisore; George Areba (International Journal of Social Science, 2023)
The urgency with which climate change education is required demands massive coordination across all formal education systems (primary, secondary and tertiary institutions), non-formal systems (community-based and non-governmental organisations), and informal systems (museums, over the radio, in libraries, or bus stops). It also demands attention from individuals in both low and high-carbon emitting countries, as well as within and across sectors (education, energy, agriculture, transportation and urban planning). Rather positively though, education has a ripple effect that goes beyond the individual learner and has the potential to build greater environmental enlightenment and concern amongst family members and communities. Accordingly, education (formal, informal and non-formal) would also help individuals and communities build resilience and lessen their vulnerabilities to a rapidly changing climate. Hence, this paper explores the barriers that impede enhanced climate change education with a view to helping surmount them and enlighten learners and communities at large, on the dangers of climate change and strategies of minimising human activities that bring about or accelerate climate change, even as communities get sensitised on resilience measures. Accordingly, the barriers to effective climate change education as determined by this review are inadequate political leadership, low eco-literacy levels, cognitive challenges, scepticism of scientific evidence, misinformation and disinformation of facts about climate change, limited knowledge and skills to impart to learners during climate change instruction, moral and behavioural challenges and psychological and social barriers. It is thus, recommended that salient aspects of climate change be integrated into teacher-training curricula worldwide and policies be enacted aimed at mitigating scepticism and disinformation concerning climate change. Furthermore, coordination of efforts between the private sector, government, community members and civil society to promote climate change education is strongly recommended together with the adoption of transformative learning that results in perspective and behaviour change